INCREASING KNOWLEDGE AND TEETH-BRUSHING THROUGH APPLICATIONBASED EDUCATION GIGI.ID IN ELEMENTARY SCHOOL STUDENTS - Hermien Nugraheni; Diyah Fatmasari; Ani Subekti (Poltekkes Kemenkes Semarang, 2023)
Even though 94.2% of people have brushed their teeth every day, only 2.3% did it at the right time, namely after breakfast and before going to bed at night. This has an impact on the emergence of dental health problems, namely caries. Caries can affect the level of health in the process of growth and development and the future of children, such as a decrease in children's learning ability which can affect learning achievement. This educational activity aims to enable target students to keep their teeth and mouth clean, they can be disciplined in caring for their teeth, using the GIGI.ID application. This educational activity was carried out in collaboration with PT. Senyum Sehat Indonesia provides education about dental health using the GIGI.ID application is the first telemedicine application that focuses on dental and oral health in Indonesia. GIGI.ID is a digital social enterprise startup that focuses on equal access to promotive and preventive health, especially dental and oral health for the people of Indonesia. The location of this community service activity is SD Negeri Seberang Masjid 1 Banjarmasin. Students, parents, and teachers understand the process of dental caries, and actions to prevent damage to teeth, and can practice how to brush their teeth properly and use the GIGI.ID application to get information about dental health care. Students know how important it is to maintain healthy teeth and mouth, and are able to practice how to brush their teeth properly.